PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. BANK NEGARA INDONESIA (PERSERO) TBK CABANG UTAMA BALIKPAPAN - Aldi Ramadhani, Muhammad; Hadiyatno, Didik; Yuliani, Tutik (Fakultas Ekonomi Universitas Balikpapan, 2024)
Muhammad Aldi Ramadhani (2024), The Influence of Compensation, Work Environment, and Leadership Style on Employee Performance PT. Bank Negara Indonesia (Persero) Tbk Balikpapan Main Branch. Supervisor I Mr. Didik Hadiyatno, and Supervisor II Mrs. Tutik Yuliani. The purpose of this research is to determine the influence of compensation, work environment and leadership style on employee performance at PT. Bank Negara Indonesia (Persero) Tbk Balikpapan Main Branch. This type of research is quantitative using purposive sampling techniques with the criteria of permanent employees, the number of respondents was 68 people by distributing questionnaires. Researchers use SmartPLS 4.1.0. Data calculation methods using Validity Test, Reliability Test, Research Hypothesis Test, F-Square Test and R-Square Test. The research results show that the Compensation variable (X1) has a positive and significant effect on Employee Performance (Y), the Work Environment (X2) has a positive and significant effect on Employee Performance (Y), and Leadership Style has a positive and significant effect on Employee Performance (Y).